A comparative study of treatment modalities in female androgenetic alopecia - U., Mansuri Uzzaif; Vaaruni, Ravishankar; S., Parmar Kirti; J., Shah Bela (International Journal of Research in Medical Sciences, 2016)
Background: Androgenetic alopecia (AGA) occurs in both men and women. It is characterized by progressive loss of hair from the scalp in a defined pattern. The aim of the study was to analyse and assess the efficacy of treatment modalities in female androgenetic alopecia (AGA) and assess the side effects, level of stress, associated family history and past history of any medical illness in these patients. Methods: 60 female patients between 18-50 years of age were randomly divided into 2 groups, with 30 cases in each. The first group (Group A), received only topical 2% minoxidil, applied in the form of a 1 ml solution at an interval of 12 hours and the second group (Group B), received combination of 2% minoxidil and platelet rich plasma (PRP) therapy injections every 15 days for 2 months and then every monthly for 4 months. Patients were evaluated every 2 months for a period of 6 months based on patient and physician assessment of clinical improvement, photographic evidence and type of hair growth. Side effects during the treatment period were observed for. Results: 70% (n=42) of patients were in the age group 18-30 years. 56.67% (n=34) had alopecia of Ludwig pattern type 2. Hypothyroidism was the major associated medical illness seen in 20% (n=20) of patients. Family history was seen in 46.66% (n=28). 73.33% (n=44) had stress in the range of 5-7 on a visual analogue scale (VAS) of 10. Excellent improvement was observed in 33.33% of patients of Group A (Minoxidil only), and in 60% (n=36) of patients of Group B (Minoxidil + PRP). Pruritis was the most common side effect seen in 13.33% (n=8) patients. Conclusions: Non-invasive management for AGA is a safe, effective and promising tool for hair growth. It offers better patient compliance, less side effects and only topical anesthesia is required. Multimodality approach in the treatment of hair loss gives excellent response, which is seen in our study as combination therapy (2% minoxidil with PRP) is more effective than topical minoxidil alone.